Alterações morfológicas em plantas do gênero Urochloa P. Beauv. submetidas a três condições de umidade do solo. - Macedo, Lucas Chagastelles Pinto de (2015)
Rice is a very important crop for the Rio Grande do Sul state. The productivity of this crop is affected by several factors, and competition with weeds, one of the main responsible for losses in production. Among the weeds occurring in rice crops, grasses are the main competitors with culture. Urochloa plantaginea and Urochloa platyphylla are the two species of the genus Urochloa, which are found infesting areas which produces rice. Both species are described as occurring in drier environments, although U. platyphylla, can also be found in moist environments. Since these species are naturally occurring in environments with small amounts of water, but have been found in rice production areas, which are characterized by containing high amounts of water in the soil, this study aimed to evaluate and quantifying plant which morphophysiologic parameters are altered when they are subjected to developing in environments with different amounts of water. The experiment was conducted in a greenhouse, where controlled irrigation daily, keeping the experimental units with different amounts of water. Each species was subjected to develop in the water condition in 50% of field capacity, 100% of field capacity and under water depth of 5 cm. During the experiment, there was the collection of plant material root, stem and leaf, for making slides and evaluation of the anatomical behavior of each species under each condition, as well as measures of vegetative and reproductive characters. The results obtained in this experiment show that both types complete their life cycle in the three different amounts of water in the environment. There were statistically significant differences in the duration of the cycle of each type. Urochloa plantaginea had larger cycle when developed under the condition of 50% of field capacity, while U. platyphylla showed higher cycle on condition of water depth. The condition of water depth led the two species the first issue the inflorescences, occurring shorten the growing season. The dry weight of shoots levels was higher for both species when grown under the condition of 100% of field capacity. The less water (50% of field capacity) promoted root growth for both species, occurring higher dry matter yield in this. The results of anatomical analyzes show the increased aerenchyma formation for the two species, as it increases the amount of water in the soil. Under water depth there was greater diameter of aerenchyma and smaller diameter of the leaf mesophyll and root central cylinder. In relation to the stem, the condition of water depth increases the diameter of the fistula and reduces the number of cortical aerenchyma.